The Duality of Cozy Games: Cozy Agency, Neoliberalism, and Affect - Bódi, Bettina (Replay. The Polish Journal of Game Studies, 2024)
Cozy games can be thought of both as indoctrination into, and escapism from, anxieties caused by neoliberal ideology underpinning the late-capitalist apparatus championing productivity, progress, and quantifiable result generation. I draw on sociologist Anthony Giddens’ notion of “ontological security” – which refers to our sense of stability and safety that we draw from continuous, and therefore reliable, predictable, unthreatening, and familiar sequences of events or activities happening in our everyday lives – and propose the concept of “cozy agency” to productively examine the aesthetics of games that are not characterized by a hypermasculine drive to successfully overcome challenges, nor by the inessentiality of player action typical of idle games. Research on lifestyle media, cuteness, and vegetal affect is put into dialogue to theorize the modalities of agency typical cozy game aesthetics can afford and constrain. Such an approach is in line with recent shifts in discourses of agency and interactivity in game studies, which criticize these two terms for being too binary, masculine, and not accommodating alternative forms of engagement with games, with recent scholarship on agency especially calling for a politicization of the term and a call to delve into the significance of meaningful empowerment to act in/with/on/through games.